Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/02755947.2015.1052163
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Growth, and Tag Retention in Age‐0 Chinook Salmon Implanted with 8‐, 9‐, and 12‐mm PIT Tags

Abstract: The ability to represent a population of migratory juvenile fish with PIT tags becomes difficult when the minimum tagging size is larger than the average size at which fish begin to move downstream. Tags that are smaller (e.g., 8 and 9 mm) than the commonly used 12‐mm PIT tags are currently available, but their effects on survival, growth, and tag retention in small salmonid juveniles have received little study. We evaluated growth, survival, and tag retention in age‐0 Chinook Salmon Oncorhynchus tshawytscha o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 32 publications
8
53
0
Order By: Relevance
“…A complementary approach to the otolith reconstructions recommended above to assess the lifetime survival and habitat use of SRWRC too small to acoustically tag (Advancement 3), is to tag representative sizes of juveniles with PIT tags throughout the monitoring program or within specific restoration sites. For example, only 8% of the juvenile salmon collected at Knights Landing RST were > 80 mm (the approximate size cutoff for current Juvenile Salmon Acoustic Telemetry System, JSAT, acoustic tags), and 58% met the size threshold for PIT tags (> 40 mm for 8-mm tags; Tiffan et al 2015, see "Notes"; Table 3). Many juvenile SRWRC-sized fish can be sampled for genetic tissue (run ID; Advancement 1) and, because PIT tags are not limited…”
Section: Recommendationsmentioning
confidence: 99%
“…A complementary approach to the otolith reconstructions recommended above to assess the lifetime survival and habitat use of SRWRC too small to acoustically tag (Advancement 3), is to tag representative sizes of juveniles with PIT tags throughout the monitoring program or within specific restoration sites. For example, only 8% of the juvenile salmon collected at Knights Landing RST were > 80 mm (the approximate size cutoff for current Juvenile Salmon Acoustic Telemetry System, JSAT, acoustic tags), and 58% met the size threshold for PIT tags (> 40 mm for 8-mm tags; Tiffan et al 2015, see "Notes"; Table 3). Many juvenile SRWRC-sized fish can be sampled for genetic tissue (run ID; Advancement 1) and, because PIT tags are not limited…”
Section: Recommendationsmentioning
confidence: 99%
“…However, most of those studies examined the potential impacts of tagging larger fish with 12-mm and longer tags. Recent studies with shorter tags (Ouedraogo et al 2014;Tiffan et al 2015) found that approximately 640-mg (wet mass) Nile Tilapia Oreochromis niloticus and 40-49-mm FL Chinook Salmon Oncorhynchus tshawytscha that received 8-mm PIT tags had slightly suppressed growth rates for the first 4 and 7 d but that survival (93.3% and 100%) and tag retention (96.6% at 35 d; 95% at 28 d) were high. Additionally, Ward et al (2015) found no difference in TL between PIT-tagged (8-mm PIT tag) and visible implant elastomer-tagged Humpback Chub Gila cypha as small as 40-49 mm TL.…”
mentioning
confidence: 99%
“…; Tiffan et al. ). As technology continues to advance and as PIT tags become smaller, they are increasingly being used on smaller‐bodied fishes.…”
mentioning
confidence: 98%
“…; Tiffan et al. ) and as small as 35 mm FL (O'Donnell and Letcher ). Several studies have indicated that juveniles and small‐bodied species (<100 mm TL) belonging to several families, including Cyprinidae, Cottidae, Lotidae, and Percidae, can also be PIT‐tagged with no adverse effects (Baras et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation